(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2023)
The book promotion of the Macedonian translation of Time Shelter (mk. Zasolnište na vremeto; bg. Vremeubezhishte) by Georgi Gospodinov in Skopje in early December 2022 was undoubtedly the cultural event of the day in the capital of North Macedonia. Gospodinov, arguably the most prominent contemporary Bulgarian writer, and his latest novel—soon to become the first Bulgarian-language work to win the International Booker Prize in 2023—were welcomed by Macedonian readers with a fervor more commonly reserved for music stars or sports idols. Time Shelter, another of Gospodinov’s explorations of the entanglements of past and present—consistently and timely translated into Macedonian—depicts “clinics of the past,” spaces in which different decades of recent history are meticulously reconstructed and preserved. The idea evolves from a Zurich-based Alzheimer’s clinic, where patients are permanently immersed in the atmosphere of the middle-class 1960s, into a broader European (Union)-level project. What begins as therapeutic nostalgia quickly escalates into a political experiment. As tensions intensify, European nations organize referendums asking citizens which decade they would prefer to return to and inhabit. The consequences are devastating: Bulgarian society fractures along the fault lines of competing past decades, while Europe teeters on the brink of a second First World War. Within this dystopian scenario, Gospodinov poses a disquieting question: how much of the past can a single person endure? (Gospodinov 2021: 55).